Training of civil servants in Afghanistan: a case study Of Independent Directorate Of Local Governance (IDLG), Kabul - Folady, Noor Muhammad Nuzhat (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2020.